QUALITY ANALYSIS OF LIQUID WASTE AT THE BLOOD TRANSFUSION UNIT OF SOUTH SULAWESI - Andi Alim; Adam Badwi; Amalia Amalia (The Indonesian Journal of Public Health, 2021)
This study aimed to determine the quality of liquid waste at the Blood Transfusion Unit of South Sulawesi based on the parameters of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and total coliform. This study was conducted with an observational method with a descriptive approach. The results showed that BOD levels that had been processed (44.28 mg/L) and not been processed (429.89 mg/L) were eligible. COD levels that hadnot been processed (1071.42 mg/L) and those that had undergone processing (107.14 mg/L) were not yet eligible, and Total Coliforms that had not undergone processing 3,500,000 MPN/100 ml and that had undergone 2400 MPN/100 ml were eligible. Based on these three parameters, this study discovered that one of the parameters, the COD parameter was not eligible.Keywords: quality of liquid waste, BOD, COD, total coliform